Analysis of Factors Affecting the Performance of Stock Investment Portfolios in Indonesia - Thomas Nadeak; Ikaputera Waspada; Maya Macia Sari (Westscience Press, 2024)
Indonesia's capital market is experiencing rapid growth, attracting investors to invest in stocks. The performance of a stock investment portfolio is influenced by a variety of internal and external factors. Understanding these factors is important for investors in making informed investment decisions. This study aims to analyze the factors that affect the performance of stock investment portfolios in Indonesia using the literature review method. The literature review method allows for a systematic review of relevant literature and produces comprehensive findings. The results of this study are expected to provide a clear picture of the factors affecting the performance of stock investment portfolios in Indonesia and become a reference for investors in making more informed and measurable investment decisions.